2018
DOI: 10.1038/s41598-018-34427-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background and window of exposure contribute to thyroid dysfunction promoted by low-dose exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin in mice

Abstract: Genetic and environmental factors contribute to thyroid diseases. Although still debated, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is thought to induce thyroid dysfunction in humans and rodents. The data here reported point out the contribution of the exposure window and genetic background in mediating the low-dose TCDD effects on thyroid. Indeed, early (from E0.5 to PND30) and low-dose (0,001 μg/kg/day) TCDD exposure reduced the circulating fT4 and altered the expression of thyroid specific transcripts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…TCDD has been found to decrease TH levels, T4, and thyroid function. However, more studies are needed for better understanding of the mechanism of TCDD toxicity on bone through thyroid hormone signaling [107].…”
Section: Mechanisms Of Endocrine Disruption and Bone Damagementioning
confidence: 99%
“…TCDD has been found to decrease TH levels, T4, and thyroid function. However, more studies are needed for better understanding of the mechanism of TCDD toxicity on bone through thyroid hormone signaling [107].…”
Section: Mechanisms Of Endocrine Disruption and Bone Damagementioning
confidence: 99%
“…The small increase in tshb, which regulates the expression of the thyroid-specific genes such as scl5a5, suggests that other pathways might be involved, such as NF-kB. We have proposed it as a regulator of scl5a5 expression in mice exposed to p-dioxin and have shown that CPF reduces p65 nuclear level in rat follicular cells (Reale et al 2018(Reale et al , 2019. The results found in F2-larvae provide evidence that parental exposure might itself cause the reduction of the number of follicles and hypothyroidism, although we cannot distinguish between the impairment of the TH reserve in the yolk or germline epigenetic changes.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…The mechanisms of such activity are strongly debated, although increased thyroid-stimulating hormone (TSH) levels and oxidative stress have been described as endogenous factors contributing to the rise in thyroid cancer incidence. Notably, both are increased after exposure to EDCs such as Bisphenol A (BPA) [5] or TCDD [6]. Furthermore, signalling pathways, deeply involved in thyroid carcinogenesis, are also deregulated by the same factors [7,8].…”
Section: Introductionmentioning
confidence: 99%